Broadband Access Communication Technologies XIII 2019
DOI: 10.1117/12.2516013
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber for 1310nm single-mode and 850nm few-mode transmission

Abstract: In this paper, we present an optical fiber that is single-mode at 1310 nm window and few-mode at 850 nm window with high bandwidth. The fiber is compatible with standard single-mode fiber at 1310 nm, which can meet long reach requirements for hyper-scale data centers. In addition, the fiber can be used for few-mode transmission at 850 nm using single-mode or few-mode VCSELs, providing low-cost solutions for short links. We discuss fiber design considerations and present fiber properties and 25 Gb/s transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…• Two-mode FMF based on standard single-mode fiber: Through a series of systematic studies in [16][17][18]21] and the current work, we have explored the novel properties of standard single-mode fiber used in somehow unexpected regime when the operating wavelength is from 850 nm to 1060 nm or below the cable cutoff of the fiber. It can be confusing that the study addresses the two-mode property of the fiber while the fiber is referred to as a 'single-mode' fiber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Two-mode FMF based on standard single-mode fiber: Through a series of systematic studies in [16][17][18]21] and the current work, we have explored the novel properties of standard single-mode fiber used in somehow unexpected regime when the operating wavelength is from 850 nm to 1060 nm or below the cable cutoff of the fiber. It can be confusing that the study addresses the two-mode property of the fiber while the fiber is referred to as a 'single-mode' fiber.…”
Section: Discussionmentioning
confidence: 99%
“…In the 850 nm to 1060 nm range, which is of particular interest for VCSEL transmission, the fiber operates as a two-mode fiber with LP01 and LP11 modes. Recent research has demonstrated that standard single-mode fibers with graded-index profiles can achieve a high bandwidth at around 850 nm, enabling data transmission at rates of 25 Gb/s over distances of up to 1500 m [16,17]. Similarly, standard single-mode fibers with step-index profiles also exhibit two modes within the 850 nm to 1060 nm range.…”
Section: Introductionmentioning
confidence: 99%
“…Where 𝑎 is parameter which represents the refractive index profile of MMF's core. For 𝛼 = 1, is a triangular profile, if 𝛼 = 2 is the parabolic profile, and for 𝛼 > 10, is a step index profile [22].…”
Section: Principle and Experimental Methodsmentioning
confidence: 99%
“…Fiber single-mode pengkondisian modal khusus juga dapat dirancang untuk integrasi dalam adaptor kompak . Fiber single-mode digunakan di pusat data untuk aplikasi jarak pendek dan jarak jauh karena transmisi mode tunggal (SM) mampu menghasilkan bandwidth sistem yang tinggi dan jangkauan yang lebih jauh, pusat data berskala besar dan besar cenderung mengadopsi fiber mode tunggal standar sebagai media transmisi tunggal (Chen et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified